The Role of Sound Recording in Turn-of-the-Century Cultural Processes Through the Pedagogical Activities of Béla Bartók - Andrea Daru (Tánc és Nevelés)
The emergence of sound recording devices in the 20th century marked a breakthrough in technological advances but also radically transformed the deeper layers of our lives. An earlier study by Daru (2022) explored the differences between written and recorded music and the anthropological impact of sound recording. The present paper aims to provide a philosophical-anthropological analysis of the educational process, following Kron (2003), within the frameworks of enculturation and socialization. The first part of the paper examines the cultural, social, and artistic effects of sound recording, while the second part analyses of music and dance-related pedagogical processes from a comparative perspective. In the final sections, following Bartók’s work, I discuss the connections between folk music, dance culture, and pedagogy in the 20th century. The study aims to formulate theoretical foundations for further research.